1983
DOI: 10.1002/food.19830270529
|View full text |Cite
|
Sign up to set email alerts
|

Aroma retention in modern bread production

Abstract: In highly industrialized countries bread consumption rate decreases in favour of flavour-intensive foods like meat, sweets, cocoa products or alcoholic beverages. This trend which is unfavourable from the nutritional point of view may be forced by flavour losses in modern bread technology itself. Sensory profile studies indicate 4 points which may change the traditional bread flavour, i.e. reduction of flour extraction rate, changes within bread formula, shortening of the dough procedures or of baking time. Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

1989
1989
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 1 publication
0
15
0
1
Order By: Relevance
“…However, yeast preparations often contain LAB, especially lactobacilli rather than Pediococcus, Lactococcus and Leuconostoc spp. (Jenson, 1998), which in this case contributes only to a small degree to the acidification and aroma development of dough because of the short processing time (Rothe & Ruttloff, 1983). Starting from glucose, homofermentative LAB mainly produce lactic acid through glycolysis (homolactic fermentation) while heterofermentative LAB produce, besides lactic acid, CO 2 , acetic acid and/or ethanol (depending on the presence of additional substrates acting as electron acceptors, as reported in Fig.…”
Section: Sourdough Fermenting Microorganismsmentioning
confidence: 95%
See 1 more Smart Citation
“…However, yeast preparations often contain LAB, especially lactobacilli rather than Pediococcus, Lactococcus and Leuconostoc spp. (Jenson, 1998), which in this case contributes only to a small degree to the acidification and aroma development of dough because of the short processing time (Rothe & Ruttloff, 1983). Starting from glucose, homofermentative LAB mainly produce lactic acid through glycolysis (homolactic fermentation) while heterofermentative LAB produce, besides lactic acid, CO 2 , acetic acid and/or ethanol (depending on the presence of additional substrates acting as electron acceptors, as reported in Fig.…”
Section: Sourdough Fermenting Microorganismsmentioning
confidence: 95%
“…Because of its lack in gluten proteins, rye flour has to be prefermented before bread can be manufactured from such rye-based dough and this procedure is one of the main reasons for the differences in the overall aromas between wheat and rye breads (Kirchhoff & Schieberle, 2001). Nevertheless, sourdough fermentation is essential to achieve an acceptable flavour, since a comparison between chemically acidified bread and sourdough bread showed that the latter possessed a superior sensory quality (Kirchhoff & Schieberle, 2002;Rothe & Ruttloff, 1983). The ratio between lactic and acetic acid, defined as the fermentation quotient (FQ), is an important factor that might affect the aroma profile, although it is also relevant for the structure of final products.…”
Section: Contribution Of Lactobacilli To Flavour Developmentmentioning
confidence: 98%
“…Special bread technologies have been characterized on the basis of the flavour compounds (7,8) and a differentiation of the crumb and crust contents has also been reported (1,9). Even though the largest amounts of aroma substances are formed during baking (10), sourdough fermentation is essential in achieving an acceptable flavour, since chemically acidified bread failed in the sensory quality (11). The content of volatiles has been investigated in spontaneously started bakery sourdoughs (11) and in sourdoughs fermented with pure commercial starter cultures (6).…”
Section: Introductionmentioning
confidence: 98%
“…Even though the largest amounts of aroma substances are formed during baking (10), sourdough fermentation is essential in achieving an acceptable flavour, since chemically acidified bread failed in the sensory quality (11). The content of volatiles has been investigated in spontaneously started bakery sourdoughs (11) and in sourdoughs fermented with pure commercial starter cultures (6). No reports have widely characterized the volatile compounds produced by the individual sourdough bacterial and yeast species with a differentiation among the strains.…”
Section: Introductionmentioning
confidence: 99%
“…The mixing and fermentation processes play an important role in determining the qualities of white bread. Numerous studies have been carried out on the aroma and flavor of white bread-complex flavor compounds derived from raw materials and the fermentation and baking processes (Baltes et al, 1994;Chang et al, 1995;Collyer, 1964;Grosch et al, 1997;Heidelberg et al, 1996;Henry et al, 1996;Hwang et al, 1994;Maga, 1974;Mulders, 1973;Rothe et al, 1983;Schieberle et al, 1989;Schieberle et al, 1991a;Seits et al, 1998). Flavor compounds produced by microorganisms such as bread yeast during the fermentation process markedly affect the flavor compounds produced during the subsequent baking process as the most important factor of the characteristic flavor of white bread (Watanabe, 1997).…”
Section: Introductionmentioning
confidence: 99%